2019
DOI: 10.18261/issn.1891-943x-2019-01-02-04
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ experiences with theuse of a student response system when learning physiology

Abstract: Digitisation has become a part of quality education and can help change the teacher's role from a lecturer to a supervisor, encourage a more student-centred approach, and increase the interactivity between the teacher and the students. However, it can be challenging to facilitate more interactive pedagogy in large classes. The aim of this study was to gain knowledge about nursing students' experience with the use of a student response system (SRS) in learning activities when learning physiology. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Our study shows that the use of an SRS promoted participation in larger groups when the questions were challenging and that it supported experiences of community, confidence, confirmation and feedback, which is in accordance with the findings of previous research (Bingen et al., 2019; De Gagne, 2011; Nelson et al., 2012). Our students stressed that they appreciated the opportunity to use the SRS to give feedback to the teacher, who could then adapt the teaching to their knowledge level and clarify misconceptions.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study shows that the use of an SRS promoted participation in larger groups when the questions were challenging and that it supported experiences of community, confidence, confirmation and feedback, which is in accordance with the findings of previous research (Bingen et al., 2019; De Gagne, 2011; Nelson et al., 2012). Our students stressed that they appreciated the opportunity to use the SRS to give feedback to the teacher, who could then adapt the teaching to their knowledge level and clarify misconceptions.…”
Section: Discussionsupporting
confidence: 92%
“…The teaching design is implemented iteratively and occurs over at least two cycles; in the present study, we examined cycle 2, focussing on on‐campus activities and experiences of mastery. Cycle 1 (the pilot) (Bingen et al,2019) and experiences of off‐campus activities in cycle 2 have been previously reported on (Bingen et al, 2019).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Wang, Ran, Huang and Swigart (2019) further introduced game-based elements to SRS and found that this is highly favoured by students. Bingen, Tveit, Krumsvik and Steindal (2019) also used SRS for nursing students and received positive feedback from them.…”
Section: Introductionmentioning
confidence: 99%